Performance and parasite control of different genetic groups of lambs finished in irrigated pasture - Fernandes Júnior, G. A. [UNESP]; Lôbo, R.N. B.; Vieira, L. S.; Sousa, M. M.; Lôbo, A. M. B. O.; Facó, O. (Universidade Federal de Minas Gerais, Escola de Veterinária, 2015)
The aim of this study was to compare the following four genetic groups of hair sheep: Santa Inês (SI), Morada Nova (MN), Brazilian Somali (BS), and the F1 1/2Dorper x 1/2Morada Nova crossbreed on traits related to growth and parasitic infection. Thirty-three male lambs of the same age and of simple birth, under the same pre-weaning management conditions were used in the experiment. After weaning the animals were housed in a completely randomized design in paddocks made of Panicum maximum cv. Tanzania. Along the course of the research, the performance of the four groups of sheep was observed to be negatively affected by gastrointestinal parasites, but there was a genotype effect to the average daily weight gain (ADWG), where the SI and F1 genotypes presented higher values. The effects of genotype, time and genotype x time interaction were significant in weight and corporal score (CS) measurements. The BS lambs had the highest CS values throughout the experiment despite not presenting greater weight gain when compared to the SI and F1 breeds. There were also significant effects of time and genotype x time interaction for packed cell volume (PCV) and FAMACHA© score (FAM) and only the time effect was significant in the total number of eggs per gram (EPG) and total plasma protein (TPP). The MN lambs showed higher PCV values and unlike the other groups, presented a FAMACHA© score below 3 and PCV above 23% even having a higher EPG tendency, especially in the initial phase, indicating a possible higher resilience to infection caused by gastrointestinal parasites.

O objetivo deste estudo foi comparar quatro grupos genéticos de ovinos: Santa Inês (SI), Somalis Brasileira (SB), Morada Nova (MN) e 1/2 Dorper - 1/2 Morada Nova (F1) quanto às características de crescimento e de infecção parasitária. Trinta e três cordeiros machos, de mesma idade, nascidos de parto simples e submetidos às mesmas condições de manejo pré-desmame foram utilizados no experimento. Após o desmame, os animais foram alojados em piquetes de capim Panicum maximum cv. Tanzânia, em um sistema rotativo de pastejo sob um delineamento inteiramente ao acaso. Os resultados mostraram que, ao longo do experimento, o desempenho ponderal dos quatro grupos genéticos foi negativamente afetado pela infecção por endoparasitas, mas o efeito de genótipo foi significativo para ganho de peso médio diário, e os grupos SI e F1 apresentaram melhores médias. O efeito do genótipo, tempo e interação genótipo x tempo foi significativo para o peso e o escore corporal. Os cordeiros da raça SB apresentaram maiores escores corporais ao longo do experimento, apesar do menor ganho de peso quando comparados aos dos grupos SI e F1. Houve efeito significativo do tempo e da interação genótipo x tempo para o hematócrito e para o grau FAMACHA©. Somente efeito do tempo foi verificado para as características OPG e proteína plasmática total. Os cordeiros da raça Morada Nova, ao contrário dos demais grupos, mantiveram o grau FAMACHA© inferior a 3 e hematócrito inferior a 23%, mesmo com tendência de maior OPG, principalmente na fase inicial, indicando uma possível maior capacidade de adaptação à infecção por endoparasitas.
Desempenho e controle parasitário de diferentes grupos genéticos de cordeiros terminados em pastagem irrigada
Keywords: Hair sheep; Weight gain; Genotype effect; Ovinos deslanados; Ganho de peso; Efeito do genótipo